Produzioni fini e vasellame comune da Asculum nella fase della romanizzazione - Morsiani, Sara (Rei Cretariae Romanae Fautorum Acta, 2022)
As part of a study on the Romanization in the middle Adriatic area, I have taken into account some ceramic contexts from Ascoli Piceno (Marche/Italy). In particular, my work analyzes the complex of the former Ospedale Mazzoni, which is located on Colle dell’Annunziata, and the area of Porta Gemina, which was the main entrance of the via Salaria to Asculum. The study of black glazed pottery showed the presence of a first phase (4th–3rd century BC) with massive imports from Etruria, Lazio, Apulia and Attica, and a second phase (2nd–1st century BC) with the start of local production, whose forms look like Campana A and B. The local production of Ascoli can be easily recognized in terms of technical features because of its s quite dusty light gray clay, which is normally purified or rarely includes micaceous elements, and because of its fairly compact matt dark gray glaze. The presence of a local ceramics production is also proved by the coarse ware, showing typical Tyrrhenian forms in mixtures that show chemical affinity with the most ancient «olle picene», which were certainly local. In the two chronological phases the most documented coarse ware forms are pots with broad everted rim or almond section and starting from the 2nd century BC pans with short horizontal rim. Instead, basins/mortars, pans with «orlo bifido» and internal red slip cookware, according to their morphological and technical characteristics, seem to have been imported from the Etruscan-Lazio area.